How School Climate and Prosocial Behavior Relate to Bullying Among Junior High School Students in Sorong - Lusiagama, Sabila Bening; Utami, Adnani Budi; Haque, Sayidah Aulia Ul (Psikoislamika: Jurnal Psikologi Islam, 2025)
The study investigated the influence of school climate and prosocial behavior on bullying tendencies among junior high school students in Sorong City. A total of 370 participants were selected using cluster random sampling. The research applied a quantitative correlational approach, and data were analyzed using multiple regression techniques. Results from the coefficient of determination test revealed that school climate and prosocial behavior collectively explained 35.9% of the variance in bullying tendency (R² = 0.359). The F-test showed a significant joint effect of the two independent variables on bullying tendency (F = 102.589, p 0.01), indicating a strong overall model fit. Partial regression analysis (t-test) further confirmed that both predictors significantly influenced bullying tendency. School climate (β = –0.510, p 0.01) and prosocial behavior (β = –0.196, p 0.01) negatively and significantly predicted bullying behavior. These results suggest that students who perceive a more positive school environment and demonstrate higher levels of prosocial behavior tend to exhibit lower levels of bullying. The findings support the importance of fostering positive social environments and enhancing prosocial values in school-based interventions to effectively reduce bullying behavior.